A reverse-phase protein microarray-based screen identifies host signaling dynamics upon Burkholderia spp. infection - Chiang, Chih-Yuan; Uzoma, Ijeoma; Lane, Douglas J.; Memišević, Vesna; Alem, Farhang; Yao, Kuan; Kota, Krishna P.; Bavari, Sina; Wallqvist, Anders; Hakami, Ramin M.; Panchal, Rekha G. (Frontiers in Microbiology, 2015)
Burkholderia is a diverse genus of gram-negative bacteria that causes high mortality rate in humans, equines and cattle. The lack of effective therapeutic treatments poses serious public health threats. Developing insights toward host-Burkholderia spp. interaction is critical for understanding the pathogenesis of infection as well as identifying therapeutic targets for drug development. Reverse-phase protein microarray technology was previously proven to identify and characterize novel biomarkers and molecular signatures associated with infectious disease and cancer. In the present study, this technology was utilized to interrogate changes in host protein expression and phosphorylation events in macrophages infected with a collection of geographically diverse strains of Burkholderia spp. The expression or phosphorylation state of 25 proteins was altered during Burkholderia spp. infections of which eight proteins were selected for further characterization by immunoblotting. Increased phosphorylation of AMPK-α1, Src, and GSK3β suggested the importance of their roles in regulating Burkholderia spp. mediated innate immune response. Modulating the inflammatory response by perturbing their activities may provide therapeutic routes for future treatments.